Design and Implementation of a Proposal Network Firewall - Kadhim, Deah J.; Hussain, Walid K. (Al-Khwarizmi Engineering Journal, 2017)
In today's world, most business, regardless of size, believe that access to Internet is imperative if they are going to complete effectively. Yet connecting a private computer (or a network) to the Internet can expose critical or confidential data to malicious attack from anywhere in the world since unprotected connections to the Internet (or any network topology) leaves the user computer vulnerable to hacker attacks and other Internet threats. Therefore, to provide high degree of protection to the network and network's user, Firewall need to be used.Firewall provides a barrier between the user computer and the Internet (i.e. it prevents unauthorized Internet users from accessing private computers and networks connected to the Internet).This paper concerned with the design and implementation of a proposal firewall system which is used to protect both individual computers and corporate networks from hostile intrusion coming through Internet. The Dual-homed host architecture has been used to implement the proposed firewall system. The designed system is constructed using Visual Basic 6.0 Language.Finally, This proposed system is built depending on the packet filtering mechanism to regulate all the packets entering and leaving the protected site using IP address and port number of the TCP packet. Also this system deals with application level and monitors all packet data (content) and maintains the firewall activity with Internet connection.